Mindfulness-based stress reduction and self-compassion among mental healthcare professionals: a pilot study - Raab, Kelley (Mental health, religion & culture, 2015)
The authors conducted a pilot study on the effects of a mindfulness-based stress reduction (MBSR) educational intervention on mental health professionals' self-compassion, perceived stress, burnout, and quality of life. Data were obtained from 22 female mental healthcare workers between the ages of 24 and 69 years who were enrolled in one of four separate 8-week MBSR courses. Pre- and post-assessment measures consisted of the Self-Compassion Scale (SCS), Maslach Burnout Inventory, and Quality of Life Inventory. The changes on the SCS total score proved significant with a p-value of .003. Within the SCS, changes were significant on four out of the six subscales. The study is unique in its use of the eight-week MBSR intervention to target mental health professionals currently working in the field, and in the examination of the specific facets of self-compassion enhanced by this type of intervention.